IMPROVING THE EFFECTIVENESS OF THE TRAINING PROCESS OF STUDENTS - Parmonov Akmal Abdupattayevich; Shokirov Shuxrat G’ayratovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The scientific article Improving the effectiveness of the training process of students explores the impact of modern technological innovations on the preparation of students. In a rapidly changing sports world, innovation is becoming a key factor for achieving outstanding results in athletics. The article examines innovative approaches and technologies, focusing on the use of information technologies, analytics and biomedical devices for monitoring physical fitness, exercise techniques and recovery after training and competitions.